Spatial Competition and Transport Infrastructure: The Case of Moscow Office Rental Market - Tatiana Mikhailova (European Regional Science Association (ERSA), 2015)
This paper studies the geography of competition on Moscow commercial real estate market. We estimate the elasticity of office rental price to the prices of competing objects as a function of the geographical distance. We found that office real estate market in Moscow, although saturated, is surprisingly local. The evidence of price competition exists primarily at a walking distance, and dies down quickly at a distances beyond one kilometer. However, if competing objects are connected by a subway line, the geographical radius of competition extends to up to three kilometers. Thus, in the case of Moscow real estate transportation infrastructure works to integrate local markets and promote competition, although the magnitude of these effects are modest.
Keywords: R32; R33; L85; 330; spatial competition; real estate; transport